Critical Discourse Analysis Online News “Omnibus Law” Job Creation Case (Teun A. Van Dijk Model) - Lisdwiana kurniati; Umi Kholidah; Novita Eka Tristiana (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
This research describes three aspects, namely, macro structure, superstructure, and micro structure of online news in Kompas, Detik, Sindo News, Republika, and Tribun omnibus job creation law. The purpose of this study was to describe the macro structure, superstructure, and microstructure of the online news discourse text of the omnibus law case. The methodological approach used in this research is descriptive qualitative, while the theoretical approach of TeunA. Van Dijk's Critical Discourse Analysis. Based on data analysis, the following results were obtained. First, critical discourse analysis of macro structure in online news, describes in general about the theme of "omnibus law" on each news topic, and in it there are important points that refer to the theme. Second, the superstructure of critical discourse interprets the theme or topic put forward by the media and the news scheme or sequence that is displayed in the news text. Third, the micro structure of critical discourse in the omnibus law online news represents the involvement of several elements of discourse, namely semantics, syntax, stylistic and rhetoric. So that the online news from the three discourse structures of Van Dijk's model, namely regarding the "Omibus job creation Law ", the theme is discussed for the situation and the survey on the rejection of the job creation law, but when the entire discourse is critically analyzed it relates to the situation, the institutions and social structures that make it up are used. to influence and emphasize certain things in one group.